1989
DOI: 10.1016/0014-5793(89)80940-8
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of a DNA region of Actinoplanes teichomyceticus conferring teicoplanin resistance

Abstract: Teicoplanin is a glycopeptide antibiotic, produced by Actinoplanes teichomyceticus, active against Gram positive bacteria and recently introduced into clinical practice. It blocks cell wall biosynthesis by inhibiting peptidoglycan polymerization. The mechanism(s) of resistance of the producer strains of this class of antibiotics have not yet been characterized. We have constructed a genomic bank of A. teichomyceticus in Streptomyces lividans. A clone from this bank, pTR168, was able to confer resistance to tei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
1997
1997

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…A vanA probe also failed to hybridize with DNA from Amycolatopsis orientalis ATCC 19795 or Actinoplanes teichomyceticus ATCC 31211, which produce vancomycin and teicoplanin, respectively (98). Cloning and sequencing of the teicoplanin resistance gene of A. teichomyceticus have confirmed that there is no nucleotide or amino acid homology with vanA or its product (263,355). It therefore appears unlikely that the van cluster has originated in these organisms.…”
Section: Enterococcimentioning
confidence: 99%
“…A vanA probe also failed to hybridize with DNA from Amycolatopsis orientalis ATCC 19795 or Actinoplanes teichomyceticus ATCC 31211, which produce vancomycin and teicoplanin, respectively (98). Cloning and sequencing of the teicoplanin resistance gene of A. teichomyceticus have confirmed that there is no nucleotide or amino acid homology with vanA or its product (263,355). It therefore appears unlikely that the van cluster has originated in these organisms.…”
Section: Enterococcimentioning
confidence: 99%